The Concept of Multicultural Education in the Perspective of Islamic Religious Education in Higher Education - Nina Aria Putri; Erina Dwi Ari Utami; Tania Citra Ana Bella; Meri Rosmiaty; Pertiwi, Ika (CV Kalimasada Group, 2025)
This study aims to analyze the concept of multicultural education from the perspective of Islamic Religious Education (IRE) in higher education. Multicultural education emphasizes respect for diversity in ethnicity, culture, religion, and social values as an integral part of the learning process. Within the context of IRE, multicultural education does not merely focus on cognitive aspects but also on cultivating tolerance, religious moderation, and appreciation for differences among students. This research employs a literature review method by examining books, scientific articles, and previous relevant studies. The findings indicate that the concept of multicultural education in Islamic teachings is closely related to the principle of rahmatan lil ‘alamin, the notion of ukhuwah (Islamic, national, and human brotherhood), as well as the values of justice and equality reflected in the Qur’an and Hadith. In the higher education setting, IRE holds a strategic role in embedding multicultural awareness through the integration of tolerance, respect for diversity, and social cooperation into teaching and learning practices. Therefore, the implementation of multicultural education in IRE can serve as a foundation for fostering social harmony and strengthening students’ national character amidst diversity in academic environments.